Práticas de leitura literária na educação infantil: como elas ocorrem em turmas de uma Umei de Belo Horizonte? - Fernanda Rohlfs Pereira (2014)
This research aimed to examine and problematize the practices of literary reading held in groups of children aged 4 and 5 years old in a Municipal Unit of Child Education in Belo Horizonte. As specific objectives, we sought to explore the routine of the classes involved in the research, the way teachers mediated the practices of literary reading, the uses of the library and also the conceptions of the teachers about the issues that surrounded their own education, literature and Early Childhood Education. The research also included a brief study of the historical perspective of early childhood education over the recognition of the rights of small children. We emphasize, in this context, the development of the main laws that led to the recognition of early childhood education as the first stage of basic education through LDB 1996. Regarding the presence of literature at Umei some theorists such as Hunt (2010), Colomer (2003, 2007), Coelho (1991, 2000), Reyes (2010), Patte (2012), Cademartori (2009) and Cosson (2011) have assisted in the task of conceptualizing key aspects to this research, for example, the definition of children's literature and the importance of mediation of literary reading in early childhood. Since the library was also the focus of analysis, we point out aspects of its design, the specificity of the library in the school context, based on new studies that are outlined on the library for children under six: Bebeteca. Understanding that the books that arrive at public institutions come from public policy to encourage reading, we briefly present an overview of those that stand nowadays. The research was grounded in qualitative analysis procedures, in which, firstly, we sought to delineate a general profile of daily activities conducted in the classes analyzed. Then, the analysis was vertical with the intent to understand how the practices performed by teachers involved literary reading. Finally, through semi-structured interviews, we draw a general profile of the teachers regarding the uses of literature. The final results show that children's literature is more present in speech than in the practice of teachers, which was found in the observation of literary reading proposals and book choices that were presented in these readings activities, which mostly fall short of what literature offers to Kindergarten children.